2006
DOI: 10.1523/jneurosci.1794-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

An Acute Effect of Neuregulin 1β to Suppress α7-Containing Nicotinic Acetylcholine Receptors in Hippocampal Interneurons

Abstract: We examined rapid effects of neuregulin (NRG) on nicotinic acetylcholine (ACh) receptors in interneurons located in the stratum radiatum of the hippocampus. Two types of response were detected by whole-cell recordings after brief pulses of ACh. One type was a rapidly rising and falling (monophasic) current that was blocked by methyllycaconitine. The other type was a similar fast response followed by a more slowly rising and falling current. The slow component of the biphasic response was resistant to methyllyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 48 publications
1
42
0
Order By: Relevance
“…Importantly, there is a lowered level of neuregulin in the synaptic complex isolated from the brain of schizophrenics [152,154]. The effects of neuregulin are not likely to be exclusively on glutamatergic transmission, as nicotinic and GABAergic transmission are also affected [155][156][157].…”
Section: Nrg1mentioning
confidence: 99%
“…Importantly, there is a lowered level of neuregulin in the synaptic complex isolated from the brain of schizophrenics [152,154]. The effects of neuregulin are not likely to be exclusively on glutamatergic transmission, as nicotinic and GABAergic transmission are also affected [155][156][157].…”
Section: Nrg1mentioning
confidence: 99%
“…4E, NRG2 results in phosphoactivation of PKCγ but not PKCα/βII. To selectively block PKC activation, we included an inhibitory PKC (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) peptide (10 μM) in the intracellular solution. As illustrated in Fig.…”
Section: Nrg2 Alters Gabar Currents Through Clathrin-dependent Endocymentioning
confidence: 99%
“…Reduction in forebrain NMDA receptors has been reported in TM-NRG1 mutants (Stefansson et al, 2002) and abnormalities in social behaviour have been reported in hypomorphic NMDA mutants (Mohn et al, 1999;Duncan et al, 2004); however, these studies did not resolve sociability vs social novelty. There is also evidence for α7 nicotinic acetylcholine receptor [α7nAChR] dysregulation in schizophrenia (Leonard and Freeman, 2006;Olincy et al, 2006), for NRG1 modulation of α7nAChR currents (Chang and Fischbach, 2006) and for the involvement of the α7nAChR in social recognition (van Kampen et al, 2004). Regarding the long-standing dopamine [DA] hyperfunction hypothesis of schizophrenia (Kapur et al, 2005;Seeman et al, 2006), NRG1 can regulate aspects of DAergic neurotransmission (Yurek et al, 2004) and DAergic dysfunction, particularly in the medial prefrontal cortex, has been implicated in the detection of salient social and non-social stimuli (O'Tuathaigh et al, 2003;Bassareo et al, 2002;De Leonibus et al, 2006).…”
Section: Nrg1 and Schizophreniamentioning
confidence: 99%